Social-Cognitive Determinants of HIV Testing Among Tuberculosis Infected Patients in Kassala State, Sudan - Idris, Almutaz M.; Crutzen, Rik; Van den Borne, Hubertus W. (Frontiers in Public Health, 2021)
Background: Use of HIV testing and counselling (HTC) services remains low among TB patients in Sudan. Identifying the social-cognitive (sub) determinants associated with HTC uptake is essential before developing interventions to promote uptake. This study aims to assess the sub-determinants of intention to use and actual behaviour of using HTC services among TB patients in Sudan and to ascertain the most relevant beliefs to inform future interventions. Methods: A cross-sectional study was carried out in five health facilities selected randomly in Kassala State. First, a small elicitation study (N = 25) was conducted to inform the Reasoned Action Approach (RAA) based questionnaire. A total of 411 TB patients completed the survey questionnaire. Confidence Interval Based Estimation of Relevance analysis (CIBER) was employed to establish the sub-determinants' relevance. Result: The studied beliefs explained 38–52% of the variance in the intention and 20–35% in the behaviour variance. The beliefs that “Using HTC services increases my fear of being tested positive for HIV” and “Using HTC services increases my fear of losing my partner if I have a positive test result” were negatively associated with intentions and use of HTC services; and both were highly relevant for intervention. The belief “If I use HTC services, I would know my HIV status” was positively associated with intentions and use of HTC services. However, it was less relevant for intervention. Perceived susceptibility to HIV infection was not associated with intention and only weakly associated with use of HTC services. Its relevance was low for intervention. Conclusions: The study showed that the social-cognitive beliefs (sub-determinants) vary in their relationship with the intention and use of HTC services among TB patients; with variable relevance for intervention. Interventions to enhance the use of HTC services should address the most relevant beliefs to maximise the effectiveness of interventions. Further studies are needed to identify other relevant sub-determinants of HTC use behaviour.